Optimal H2 Output-Feedback Control of Sampled Systems. Issue 30 (2016) - Amorim, Matheus F.; Gonçalves, Alim P.C.; Souza, Matheus
Abstract: This paper addresses the problem of output feedback control with limited data-rate constraints. These communication constraints may affect the transmission of control signals or measurements, giving rise to three different structures: LSRA (local sensor - remote actuator), RSLA (remote sensor - local actuator) and RSRA (remote sensor - remote actuator). The interconnection between plant and controller is a Hybrid System whose stability and H 2 performance can be determined in terms of necessary and sufficient Linear Matrix Inequalities. However, for the design of the appropriate feedback gains, those conditions become non-convex and we propose an approach to obtain suboptimal solutions based on a Cone Complementarity algorithm. Numerical examples are included.